Sodium bicarbonate microcapsule foaming agent and preparation method thereof
PVA-coated sodium bicarbonate microcapsules were prepared by spray drying and used in combination with AC foaming agent, which solved the problems of low decomposition temperature and poor dispersion in the polymer foaming industry, achieving more efficient foaming effect and better mechanical properties.
Patent Information
- Application Number
- CN202411630456.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
AI Technical Summary
As an inorganic foaming agent, sodium bicarbonate has problems such as low initial decomposition temperature, wide decomposition temperature interval, and poor dispersion in the polymer foaming industry, which limits its application. The existing microencapsulation technology is difficult to accurately control the decomposition temperature and improve dispersion, and the process is complex.
Polyvinyl alcohol (PVA) coated sodium bicarbonate microcapsules were prepared by spray drying, and process parameters were optimized to improve the preparation efficiency and product quality of the microcapsules, and used in combination with azodiformamide (AC) foaming agent.
The initial decomposition temperature of sodium bicarbonate is significantly improved, the decomposition temperature range is narrowed, its dispersion and compatibility in polymer materials are improved, the production process is simplified, and the mechanical properties of foamed materials are improved.
Smart Images

Figure CN119505359A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foaming agents, and in particular to a sodium bicarbonate microcapsule foaming agent and a preparation method thereof. Background Art
[0002] As an inorganic foaming agent, sodium bicarbonate has the advantages of being green, environmentally friendly, non-toxic and harmless, and has received widespread attention in the field of polymer foaming industry. However, sodium bicarbonate itself has the problem of low decomposition temperature and wide decomposition temperature range, which limits its application in the field of polymer foaming. Specifically, sodium bicarbonate has a low initial decomposition temperature and a large decomposition temperature range, which may cause premature decomposition during the actual processing, resulting in poor plasticization effect and difficulty matching the melting temperature of many polymers. In addition, sodium bicarbonate has poor dispersibility in polymers. In order to improve these problems, the current technical means mainly use microencapsulation technology to increase the decomposition temperature of sodium bicarbonate by coating, reduce the decomposition temperature range, and improve its dispersibility in polymer materials. However, the existing microencapsulation technology still has some shortcomings, such as:
[0003] 1. Decomposition temperature: Although the initial decomposition temperature of sodium bicarbonate can be increased by microencapsulation, in the prior art, how to accurately control the decomposition temperature to meet the requirements of different materials remains a challenge.
[0004] 2. Dispersibility: Even after microencapsulation, the dispersibility of sodium bicarbonate in polymer materials may still be less than ideal, especially in some specific applications, which will affect the performance of the final product.
[0005] 3. Process complexity: Existing microencapsulation methods may be relatively complex, involving the control of multiple steps and conditions, which may lead to increased production costs and are not conducive to large-scale industrial applications. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a sodium bicarbonate microcapsule foaming agent and a preparation method thereof, so as to increase the initial decomposition temperature of the sodium bicarbonate foaming agent, narrow the decomposition temperature range, improve the dispersibility and compatibility, simplify the production process, and improve the mechanical properties of the foaming material.
[0007] In a first aspect, the present invention provides a method for preparing a sodium bicarbonate microcapsule foaming agent, which is achieved through the following technical scheme.
[0008] A method for preparing a sodium bicarbonate microcapsule foaming agent comprises the following steps:
[0009] S1. Mixing polyvinyl alcohol with deionized water and stirring until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol aqueous solution;
[0010] S2. Add NaHCO to the polyvinyl alcohol aqueous solution at a mass ratio of polyvinyl alcohol to sodium bicarbonate of 1:(1.5-6). 3 , stirring and dissolving to obtain a mixed solution of sodium bicarbonate and polyvinyl alcohol;
[0011] S3. Pump the mixed solution of sodium bicarbonate and polyvinyl alcohol into a spray dryer for spray drying to obtain polyvinyl alcohol-coated NaHCO 3 Microcapsules.
[0012] Furthermore, in step S1, the mass volume ratio of polyvinyl alcohol to water in the polyvinyl alcohol aqueous solution is 10-30 g / L.
[0013] Furthermore, in step S3, the inlet temperature of the spray dryer is 140-170°C and the outlet temperature is 80-90°C.
[0014] Furthermore, in step S3, the spray drying process is performed with a needle passing time of 0.5-2 s / time.
[0015] In a second aspect, the present invention provides a sodium bicarbonate microcapsule foaming agent, which is achieved through the following technical solution.
[0016] A sodium bicarbonate microcapsule foaming agent prepared by the above preparation method.
[0017] In a third aspect, the present invention provides a use of a sodium bicarbonate microcapsule foaming agent, which is achieved through the following technical solution.
[0018] The sodium bicarbonate microcapsule foaming agent and azodicarbonamide are used in combination for material foaming.
[0019] In a fourth aspect, the present invention provides a foaming agent, which is realized by the following technical solution.
[0020] A foaming agent comprises the above-mentioned sodium bicarbonate microcapsule foaming agent and azodicarbonamide.
[0021] Furthermore, the mass ratio of the sodium bicarbonate microcapsule foaming agent to azodicarbonamide is 1:2 to 1:3.
[0022] This application has the following beneficial effects.
[0023] (1) Optimizing the preparation process: The present invention optimizes the preparation process and improves the preparation efficiency and product quality of the microcapsules by systematically studying the process parameters of the spray drying technology for preparing the sodium bicarbonate microcapsule foaming agent, such as the air inlet temperature, spray speed, and liquid concentration.
[0024] (2) Regulating the decomposition temperature: The present invention achieves regulation of the decomposition temperature of sodium bicarbonate by precisely controlling the preparation process of sodium bicarbonate microcapsules, so that it decomposes within a specific temperature range, which offsets the exothermic reaction of the AC foaming agent and reduces the temperature during the foaming process;
[0025] (3) Improving foaming performance: The present invention uses the prepared sodium bicarbonate microcapsule foaming agent in combination with an AC foaming agent. Studies have shown that this has a positive effect on the foaming performance of the AC foaming agent, improves the foaming multiple and foaming rate, and optimizes the pore structure, thereby improving the foaming effect and stability of the AC foaming agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a physical picture of the sodium bicarbonate microcapsules prepared in the present application (wherein, a. sodium bicarbonate; b. polyvinyl alcohol; c. sodium bicarbonate microcapsules);
[0027] Figure 2 This is a polarizing microscope image of the sodium bicarbonate microcapsules prepared in the present application;
[0028] Figure 3 The DSC data graph of the sodium bicarbonate microcapsules prepared in the present application (wherein, a. DSC data graph of sodium bicarbonate and sodium bicarbonate microcapsules under constant temperature conditions; b. DSC data graph of sodium bicarbonate microcapsules with different core-wall ratios under variable temperature conditions);
[0029] Figure 4 It is a TG curve diagram of the sodium bicarbonate microcapsules prepared in the present application (wherein, a. TG curves of the core material sodium bicarbonate, the wall material polyvinyl alcohol and the microcapsules; b. TG curves of the sodium bicarbonate microcapsules with different core-wall ratios).
[0030] Figure 5 is a stress-strain curve diagram of the foamed material prepared by different foaming agents of the present invention;
[0031] Figure 6 It is a comparison chart of the ball rebound rate and density of the foamed materials made of different foaming agents of the present invention (wherein, a. the ball rebound rate of the foamed materials made of different foaming agents; b. the density of the foamed materials made of different foaming agents). DETAILED DESCRIPTION
[0032] The present invention develops a method for preparing sodium bicarbonate microcapsules coated with polyvinyl alcohol (PVA) by spray drying. This microcapsule technology can form a shell layer outside the core material, protect the original properties of the internal core material, prevent interaction with the external environment, and ensure participation in the reaction under specific conditions, thereby improving the scope of application. Specifically, the microcapsule technology uses a heat-resistant polymer material as a wall material and adopts spray drying technology to coat sodium bicarbonate of different mass proportions to prepare sodium bicarbonate microcapsules. The present invention can significantly increase the initial decomposition temperature of sodium bicarbonate and narrow its decomposition temperature range. Through microscopy, Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TG) and other methods, the microscopic morphology, material structure and thermal stability of the microcapsules can be analyzed, so as to select the microcapsules with the best comprehensive coating effect.
[0033] In specific applications, the present invention can achieve effective mixing with polymer materials by using the prepared microcapsules in combination with azodicarbonamide (AC) foaming agent to obtain better foaming structure and mechanical properties. In particular, when AC is used together with sodium bicarbonate microcapsules, the heat absorbed during the decomposition of sodium bicarbonate just offsets the heat released during the foaming process of AC, avoiding polymer degradation caused by local overheating.
[0034] On the technical level, the spray drying technology used in this application disperses the liquid material into droplets through an atomizer, and then uses hot air to contact the droplets to quickly evaporate the water in the droplets, thereby obtaining a dry product. It has the characteristics of fast drying speed, suitable for drying heat-sensitive materials, application in the production of a variety of products, good product quality and high stability.
[0035] The invention will be further described below with reference to the accompanying drawings and embodiments.
[0036] Example
[0037] A method for preparing a sodium bicarbonate microcapsule foaming agent, comprising the following steps:
[0038] 1. Prepare raw materials: prepare the required polyvinyl alcohol (PVA) and sodium bicarbonate raw materials.
[0039] Solution preparation: Use an electronic analytical balance to take 15g of polyvinyl alcohol (PVA) and add it to 500mL of ultrapure water at room temperature to form a 3g / 100mL polyvinyl alcohol aqueous solution. Stir until the polyvinyl alcohol is completely dissolved and a transparent and clear emulsion appears. Let it stand for 48 hours and wait for the bubbles in the solution to completely disappear before use.
[0040] According to the mass ratio of PVA to sodium bicarbonate of 1:1.5, 1:2, 1:5, and 1:6, 4.5 g, 6 g, 15 g, and 18 g of NaHCO were added to the polyvinyl alcohol aqueous solution, respectively.3 , stir to dissolve to obtain a sodium bicarbonate / PVA mixed solution.
[0041] 2. Preparation of spray dryer: Install all components according to the installation instructions of the spray dryer. Check whether the power supply, gas source and other connections of the equipment are normal.
[0042] 3. Start the equipment: Press the equipment start button to start the bellows and heater (note that the fan must be started before the heater is started). Set the inlet air temperature value (160℃) and the outlet air temperature value (80℃ or 90℃), and wait for the equipment to preheat to the set temperature.
[0043] 4. Spray drying: When the equipment reaches the set temperature and stabilizes, turn on the peristaltic pump (15rpm) and spray the sodium bicarbonate / PVA mixed solution through the nozzle of the spray dryer at a rate of 0.5s / time. During the spraying process, the solution will dry quickly to form sodium bicarbonate microcapsules.
[0044] 5. Collection and treatment: Collect the sodium bicarbonate microcapsules at the outlet of the spray dryer and perform screening and impurity removal treatments.
[0045] 6. Shutdown steps: When the material is used up, water is added to spray all the materials in the hose (about 5 minutes), and then the air pump and needle are turned off. Then turn off the heater and fan. When the air inlet temperature drops below 60°C, remove the collection bottle and transfer the materials to other containers. After the collection bottle is completely cooled, remove it, clean it, and dry it for the next experiment.
[0046] A small amount of sodium bicarbonate, polyvinyl alcohol, and sodium bicarbonate microcapsule samples were placed on weighing paper, and macroscopic photos were obtained by taking photos and comparative analysis. A small amount of dried sodium bicarbonate microcapsule samples were evenly placed on a glass slide, pressed, and placed in a polarizing microscope (400X) for microscopic morphology observation to obtain a picture of the microcapsule structure.
[0047] like Figure 1The three pictures a, 1b, and 1c, from left to right, are sodium bicarbonate powder (a), the second is polyvinyl alcohol powder (b), and the last is sodium bicarbonate microcapsules (c) prepared in this application with a mass ratio of 1:6 (the amount of the three pictures is 1g). By comparison, it can be seen that both sodium bicarbonate and PVA are white powders, and PVA is slightly crystalline; and the sodium bicarbonate microcapsules coated by spray drying are also white powders, but there are more lumps. This is because PVA itself has water absorption, and because the dried microcapsules are more fluffy, the gaps between the particles are increased, and water molecules are easier to penetrate, and it becomes easier to absorb and bind water, so more lumps appear. At the same time, the comparison of the three substances under the same mass condition of 1g shows that the microcapsules occupy a larger volume. With a larger volume under the same mass, the microcapsules have a smaller density (corresponding to their fluffy structural characteristics).
[0048] Polarized microscope photos of sodium bicarbonate microcapsules (the mass ratio of PVA to sodium bicarbonate is 1:6) are shown in Figure 2. Figure 2 As shown in a, the size of the obtained microcapsule particles is mostly between 1 μm and 10 μm, and the size distribution is relatively uniform. After further observation of the local powder particles, as shown in Figure 2 b and 2c, it can be seen that there are two structures in the figure: one is a clear microcapsule with a double-ring outer layer and a transparent center. This is the state of the microcapsule prepared by the present application after being wrapped with PVA to form a core-shell structure, which confirms that the method adopted by the present application to prepare the microcapsule can indeed wrap the sodium bicarbonate core material partially to form a sodium bicarbonate microcapsule. The other is irregular particles, which should be the sodium bicarbonate crystals not coated by PVA in the drying process and the uncoated dry PVA powder.
[0049] The present application also uses differential scanning calorimetry (DSC) and thermogravimetric analysis (TG) to test the prepared sodium bicarbonate microcapsules. Figure 3 , 4 shown.
[0050] By differential scanning calorimetry (DSC), the peak of the DSC curve of the microcapsules is obviously on the left side of the sodium bicarbonate ( Figure 3), the decomposition temperature range is significantly smaller than that of sodium bicarbonate, which can prove that the microcapsule has indeed reduced its decomposition temperature range. At the same time, the peak of the high ratio is further to the left than the peak of the low ratio microcapsule. This phenomenon can confirm that the PVA shell becomes thinner due to the increase in the proportion of sodium bicarbonate, so that some microcapsules with general coating effects decompose in advance; while the low ratio microcapsules are within the appropriate range, which can prove that the low ratio coating effect is better. At the same time, due to the characteristics of the microcapsules, their fluffy shape is more conducive to heat transfer, so the decomposition endothermic curve is more preferentially presented at a lower temperature to begin endothermic decomposition; while the accumulation of sodium bicarbonate is not conducive to heat transfer, the curve is backward, and it needs to be decomposed at a higher temperature.
[0051] Figure 4 For the analysis and comparison of the results of thermogravimetric (TG), although the microcapsules show two stages, stage one has already appeared at a lower temperature. This stage is mainly the weight loss of microcapsules that are not coated or have poor coating effects and the water contained in them. Stage two is the microcapsules coated with sodium bicarbonate in this experiment, and its main temperature range is within the range of 180-250℃, excluding the influence of PVA during the weight loss period; stage two is mainly the decomposition and release of sodium bicarbonate inside after the microcapsules are broken, resulting in weight loss. At the same time, after comparing the curves of several groups of microcapsules with different proportions, the low-proportion microcapsules obviously have a better coating effect. The main reason for this phenomenon is that due to the increase in sodium bicarbonate, the outer coating shell gradually becomes thinner, and the coating effect is unstable, so more weight loss is generated in stage one; and the low-proportion shell is thicker, and weight loss will only occur after being subjected to higher temperatures. And from the curve graph and coating rate, it can be seen that the microcapsules with a mass ratio of 1:1.5 have a better coating effect, and the starting decomposition temperature is significantly increased, and the temperature decomposition range is reduced compared to sodium bicarbonate. Comparing it with the results of FTIR, it can prove the relationship between the thickness of the sodium bicarbonate shell and the coating temperature. It further confirms that the sodium bicarbonate microcapsules prepared by the spray drying method in this paper have increased the decomposition temperature range and reduced the decomposition temperature range compared with the unmodified sodium bicarbonate, and increased the starting decomposition temperature in the low temperature section.
[0052] In this application, sodium bicarbonate microcapsules and azodicarbonamide (AC) foaming agent are used together to prepare foaming materials. The specific experimental steps are as follows:
[0053] (1) fully mixing sodium bicarbonate microcapsule foaming agent and azodicarbonamide in a mass ratio of 3:7;
[0054] (2) Weigh 0.2 g of diisopropyl biphenyl disulfide, 1.3 g of zinc oxide, 1.5 g of vinyl bisstearamide, 25 g of ethylene vinyl acetate copolymer, and 25 g of ethylene propylene diene monomer and mix them. Diisopropyl biphenyl disulfide is used as a crosslinking agent, zinc oxide is used as an additive, vinyl bisstearamide is used as a lubricant, and ethylene vinyl acetate copolymer and ethylene propylene diene monomer are used as base materials.
[0055] (3) Start the open rubber mixer and preheat it to 110°C. Add the raw materials mixed in step (2) between the two rollers of the rubber mixer (0.7 cm spacing between the right roller and 0.3 cm spacing between the left roller). With the rotation of the rollers and appropriate shear force, the rubber matrix material begins to be plasticized and mixed. During the rubber mixing process, gradually add the mixed powder in step (1) evenly into the rubber matrix. Continue mixing until the rubber matrix and the microcapsule mixed powder are evenly mixed to form a uniform rubber compound.
[0056] (4) Leave the refined rubber for a short period of time, and preheat the flat-plate vulcanizer to 180°C. Cut the refined rubber evenly and put it into the preheated mold. Put the mold into the flat-plate vulcanizer and vulcanize it according to the set vulcanization time (10 minutes) and temperature (180°C). During the vulcanization process, the sodium bicarbonate in the microcapsules will decompose at high temperatures to produce carbon dioxide gas, thereby causing foaming. After vulcanization is completed, remove the mold from the vulcanizer, wait for it to cool naturally, and demold it.
[0057] The mechanical properties of the foamed material prepared using the sodium bicarbonate microcapsules were tested. The specific test methods, steps and experimental results are as follows:
[0058] (1) Stress-strain curve: A punching press and a sample mold are used to prepare the required foamed sample. The prepared foamed board is placed on the plate of the punching press. The sharp side of the sample mold is placed horizontally against the foamed board. Finally, the mold and the board are pressed to obtain a sample strip for tensile testing. The foamed sample is subjected to a tensile test using a universal tensile testing machine of model TY8000A-20KN. The experimental results are shown in the figure. Figure 5 As shown in the figure, the foamed samples of pure AC and AC+sodium bicarbonate can reach the same strain with lower stress than the foamed samples of AC+sodium bicarbonate microcapsules, which indicates that the foamed samples of AC+sodium bicarbonate microcapsules are softer than the other two materials. It also reflects from the side that the foamed samples of AC+sodium bicarbonate microcapsules have more uniform pores and smaller pore sizes.
[0059] (2) Ball rebound rate: Cut a 5 cm*5 cm square foam board and place it in a BT-S-01 sponge ball rebound tester to test the ball rebound rate. The experimental results are as follows: Figure 6As shown in a, the ball rebound rate of the foamed sample obtained by AC+sodium bicarbonate microcapsules is 56.09%, which is better than the 51.33% of the pure AC foamed sample, but slightly worse than the 57.62% of AC+sodium bicarbonate. This is because the internal pores of the foamed material obtained by AC+sodium bicarbonate are larger than those obtained by AC+sodium bicarbonate microcapsules.
[0060] (3) Density: A foam material with a mass of about 1g was cut and placed in a DH-300 electronic density tester for density testing. The experimental results are shown in the figure. Figure 6 b. The density of the sample obtained by adding sodium bicarbonate and sodium bicarbonate microcapsules and mixing with AC as a foaming agent is significantly lower than that of the sample obtained by foaming with pure AC, from 0.096 kg / m 3 and 0.086kg / m 3 and 0.087kg / m 3 .
[0061] The above experimental results show that sodium bicarbonate microcapsules have potential value in the field of foaming, and the foamed samples prepared by azodicarbonamide (AC) foaming agent + sodium bicarbonate microcapsules show low hardness, high elasticity, soft texture, and small and uniform pores. These characteristics make the foaming material perform well in applications that require softness, good elasticity, and fine pores.
[0062] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a sodium bicarbonate microcapsule foaming agent, characterized in that: The following steps are involved: S1. Mixing polyvinyl alcohol with deionized water and stirring until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol aqueous solution; S2. According to the mass ratio of polyvinyl alcohol to sodium bicarbonate of 1: (1.5-6), NaHCO3 was added to the aqueous solution of polyvinyl alcohol, stirred and dissolved to obtain a mixed solution of sodium bicarbonate and polyvinyl alcohol; S3. The mixed solution of sodium bicarbonate and polyvinyl alcohol is pumped into a spray dryer for spray drying to obtain polyvinyl alcohol-coated NaHCO3 microcapsules.
2. The method for preparing a sodium bicarbonate microcapsule foaming agent according to claim 1, wherein: In step S1, the mass volume ratio of polyvinyl alcohol to water in the polyvinyl alcohol aqueous solution is 10-30 g / L.
3. The method for preparing a sodium bicarbonate microcapsule foaming agent according to claim 1, wherein: In step S3, the inlet temperature of the spray dryer is 140-170°C and the outlet temperature is 80-90°C.
4. The method for preparing a sodium bicarbonate microcapsule foaming agent according to claim 1, wherein: In step S3, the spray drying is performed by passing the needle for 0.5-2 seconds per time.
5. A sodium bicarbonate microcapsule foaming agent prepared by any one of the preparation methods of claims 1 to 4.
6. A sodium bicarbonate microcapsule foaming agent according to claim 5 and azodicarbonamide are used in combination for material foaming.
7. A foaming agent, characterized in that: The method comprises the sodium bicarbonate microcapsule foaming agent as claimed in claim 5 and azodicarbonamide.
8. A foaming agent according to claim 7, characterized in that: The mass ratio of sodium bicarbonate microcapsule foaming agent to azodicarbonamide is 1:2 to 1:3.